FORMULATION AND DEVELOPMENT OF VORICONAZOLE TABLETS CONTAINING SOLID DISPERSION WITH ENHANCED SOLUBILITY, DISSOLUTION AND BIOAVAILABILITY (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This research work enhances the solubility, dissolution and bioavailability of Voriconazole which belongs to BCS II class. Carboxymethyl tamarind gum was synthesized by using carboxymethylation of tamarind gum. Solid dispersion of Voriconazole was developed by kneading method followed by immediate release tablets. Solid dispersion characterised for solubility and instrumental analysis. Tablets were evaluated for dissolution study. Solid dispersions were confirmed by presence of distinctive peaks at 1745.58 cm-1 (C=O) and 1402 cm-1 (-COO-), using Infrared spectroscopy. The weight loss of 3.91% and 54.42 % at 100°C and in the rage of 235°C-425°C respectively was observed. 13C nuclear magnetic resonance spectrum of carboxymethyl tamarind gum displayed three distinct peaks of C1, -OH, and CH2O- group. X-ray diffraction analysis confirmed that ccarboxymethyl tamarind gum exhibits an amorphous structure. Soild dispersion of Voriconazole were developed using the kneading method, incorporating carboxymethyl tamarind gum. Compared to traditional methods, Solid dispersion formulated with carboxymethyl tamarind gum demonstrated a significant increase in solubility enhancement, ranging from 68.12 to 74.37-fold. Notably, the SD5 formulation exhibited complete release from the solid dispersion within 120 minutes. In rat models, Voriconazole levels in the bloodstream were markedly elevated with the administration of solid dispersion. Furthermore, dissolution profiles of all formulation batches showed considerable improvement. These findings shed light on effective strategies for enhancing the dissolution and bioavailability of poorly soluble drugs, thus contributing to the advancement of drug delivery systems.